2010
DOI: 10.1021/jf903530d
|View full text |Cite
|
Sign up to set email alerts
|

pH-Stability and Thermal Properties of Microbial Transglutaminase-Treated Whey Protein Isolate

Abstract: Whey protein isolate (WPI) was treated to various extents using microbial transglutaminase (MTGase) and changes in pH-stability and thermal stability of its protein components were investigated. The MTGase treatment significantly increased the denaturation temperature (T(d)) of beta-lactoglobulin in WPI, from 71.84 degrees C in the untreated sample to 78.50 degrees C after 30 h of incubation with MTGase. The enthalpy change of denaturation of WPI did not change upon cross-linking, indicating that the increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 33 publications
11
41
0
Order By: Relevance
“…Comparison of the results of the present study with those of the previous study (Agyare & Damodaran, 2010) indicate that conformational changes occurring in whey proteins under mild heat-shock conditions render them a much better substrate for MTGase.…”
Section: Mtgase-catalyzed Cross-linking Of Wpisupporting
confidence: 73%
See 4 more Smart Citations
“…Comparison of the results of the present study with those of the previous study (Agyare & Damodaran, 2010) indicate that conformational changes occurring in whey proteins under mild heat-shock conditions render them a much better substrate for MTGase.…”
Section: Mtgase-catalyzed Cross-linking Of Wpisupporting
confidence: 73%
“…Previously, it has been reported that the rate and extent of MTGase-catalyzed polymerization of a-la and b-lg in native WPI was very low over a reaction time of 44 h (Agyare & Damodaran, 2010). Comparison of the results of the present study with those of the previous study (Agyare & Damodaran, 2010) indicate that conformational changes occurring in whey proteins under mild heat-shock conditions render them a much better substrate for MTGase.…”
Section: Mtgase-catalyzed Cross-linking Of Wpisupporting
confidence: 69%
See 3 more Smart Citations